Sparsity-Based Robust Bistatic MIMO Radar Imaging in the Presence of Array Errors - Wenyu Gao; Jun Li; Daming Zhang; Qinghua Guo (International Journal of Antennas and Propagation)
A sparse recovery method for robust transmit-receive angle imaging in a bistatic MIMO radar is proposed to deal with the effect of array gain-phase errors. The impact of multiplicative array gain-phase errors is changed to be additive through model reformulation, and transmit-receive angle imaging is formulated to a sparse total least square signal problem. Then, an iterative algorithm is proposed to solve the optimization problem. Compared with existing methods, the proposed method can achieve a significant performance gain in the case that the number of snapshots is small. Simulation results verify the effectiveness of the proposed method.